Transcreation strategies of male-related traits from English online fragrance labels into Chinese: from a cultural perspective - Li, Zhu; Ang, Lay Hoon; Md Rashid, Sabariah; Mansor, Nor Shahila (Human Resource Management Academic Research Society, 2021)
In recent years, transcreation has been a buzzword in the translation industry and academia. It is defined as a combination of translation and new content creation, with translation used in its traditional sense. Although transcreation strategies have been explored, few studies have addressed whether translation or new content creation predominates in transcreation strategies and the underlying cultural reasons. This study examines the transcreation strategies involved in the Chinese translations of male stereotypes in English online fragrance labels. More specifically, as transcreation strategies can be divided into minimal and marked interventional strategies, this paper examined the cultural reasons underlying marked interventional strategies drawing on the Hofstede model. It adopts a descriptive and interpretive qualitative research method. A non-probability purposive sampling method is used to collect data. Findings illustrate that marked interventional strategies, including addition, substitution and omission, predominate transcreation strategies. Whereas minimal change including direct translation is less. The unveiled cultural reasons suggest the differences of male stereotypes in advertising between China and the US, thus contributing to the research on East-West comparison of male stereotypes. Meanwhile, it will provide implications for translators to deal with male stereotypes in advertising.